EMBLEMATIC REDUCTION IN MYKOLA KOSTOMAROV’S “SLAVIC MYTHOLOGY” - Солецький , О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The emblematic reduction in Mykola Kostomarov’s “Slavic Mythology” as well as its methodology and structurology have been interpreted in the paper. Kostomarov’s format of studies makes it possible to define the limits and the potentialities of mythological logic. This is regarded as the first stage of emblematic comprehension of the world and a man in it, the simplest visual distinction of natural ‘details’ and their explications, which will hereafter be ‘split’ by humanity’s cognitive thirst. On that ground, the awareness of the syncretic co-operation importance of the graphic associativity processes and their influence on the initial verbalisation enhances.